1988
DOI: 10.3354/meps043063
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microphytobenthos on the nutrient flux between sediment and water- a laboratory study

Abstract: The importance of microphytobenthos as a regulator of the flux of inorganic phosphorus and nitrogen between sediment and water was investigated in a laboratory study. Sediment from the SE Kattegat was incubated in nutrient-enriched seawater during exposure to varying light quantities (0, 5, 10, and 30 pE m-' S-'). Microphytobenthos growth was limited by both inorganic nutrients and light quantity. When exposed to no-light conditions, chlorophyll a content of the sediment decreased only slightly and remained at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
1
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(69 citation statements)
references
References 25 publications
2
65
1
1
Order By: Relevance
“…NH, release has either been greatly reduced compared to dark-incubation rates (Nowlcki & Nixon 1985b, Rizzo 1990 or flux direction has been reversed, with sedirnents becoming NH, sinks (Sundback & Graneli 1988, Nilsson et al 1991. The earlier study by Rizzo (1990) for a site in the York River estuary of Chesapeake Bay (USA) is of particular interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NH, release has either been greatly reduced compared to dark-incubation rates (Nowlcki & Nixon 1985b, Rizzo 1990 or flux direction has been reversed, with sedirnents becoming NH, sinks (Sundback & Graneli 1988, Nilsson et al 1991. The earlier study by Rizzo (1990) for a site in the York River estuary of Chesapeake Bay (USA) is of particular interest.…”
Section: Discussionmentioning
confidence: 99%
“…Microalgal communities can control sediment-water exchanges of nutrients through direct uptake and indirectly by oxygenating surface sediment (Andersen et al 1984, Vries & Hopstaken 1984, Nowiclu & Nixon 1985b, Asmus 1986, Kelderman et al 1988, Sundback & Graneli 1988, Keizer et al 1989, Rizzo 1990). The importance of benthic rnicroalgae as primary producers in intertidal ecosystems has long been established (Pomeroy 1959, Pamatmat 1968, Leach 1970, Riznyk & Phinney 1972, Cadee & Hegeman 1974, Gallagher & Daiber 1974, Sullivan & Daiber 1975.…”
Section: Introductionmentioning
confidence: 99%
“…High rates of ammonium flux can occur in sediments underlying natural bivalve populations (Dame et al 1989, 1991, Dame & Libes 1993, Asmus & Asmus 1991, but other factors such as microphytobenthos abundance also affect nutrient transformations and regeneration (Sundbäck & Graneli 1988, Sundbäck et al 1991. Incubation experiments have shown that particulate organic matter, oxygen conditions, and microphytobenthos abundance affect nitrogen transformations and regeneration from the sediments (Caffrey et al 1993, Enoksson 1993, Newell et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…On sandy and muddy substrates, edaphic microalgal assemblages living on a benthic surface are often dominated by diatoms (Colijn & Koeman, 1975;Colijn & Nienhuis, 1977;Admiraal et al, 1984;Colijin & De Jonge, 1984;Vos et al, 1988;De Jonge & Colijn, 1994;Agatz et al, 1999). These biofilms are particularly important in the ecology of mudflats as they exhibit high rates of primary production (Pinckney & Zingmark, 1991), influence erosion and deposition of sediment (Underwood & Paterson, 1993;Paterson, 1994), and affect sediment-water nutrient fluxes (Sundba¨ck & Grane´li, 1988;Rysgaard et al, 1995).…”
Section: Introductionmentioning
confidence: 99%